2001
DOI: 10.1002/1521-396x(200111)188:1<467::aid-pssa467>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of MOCVD and HVPE GaN Layers in H2, HCl, NH3 and N2

Abstract: This work represents a complete study of GaN annealed in H 2 , HCl, NH 3 and N 2 . The GaN thermal behavior was evaluated by comparison of MOCVD and HVPE samples. The MOCVD films were found to obey a dissociative sublimation mechanism with only gaseous species forming, while the HVPE films reacted with ambient gases to form condensed Ga in addition to the gaseous species. Differences in crystal quality for MOCVD and HVPE samples resulting from the different growth mechanisms account for the observed difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Using a NH 3 containing atmosphere is closer to the growth conditions in the MOCVD reactor and can help to stabilize the surface. However, at the same time highly reactive hydrogen can damage the surface; etching effects were observed for heat treatment of GaN in NH 3 at temperatures above 800 ºC [5]. Emission properties can also be influenced by incorporated hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Using a NH 3 containing atmosphere is closer to the growth conditions in the MOCVD reactor and can help to stabilize the surface. However, at the same time highly reactive hydrogen can damage the surface; etching effects were observed for heat treatment of GaN in NH 3 at temperatures above 800 ºC [5]. Emission properties can also be influenced by incorporated hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported earlier in [9] where a rougher surface of bulk GaN was observed after the annealing with pure H 2 at similar temperatures. Mastro et al also performed annealing of HVPE GaN layers with H 2 at different temperatures [11]. It was found that the decomposition of GaN layers started to take place at about 800 °C, via the following reaction:…”
mentioning
confidence: 99%
“…A proposed process flow of vertical GaN SBD has been shown in Figure 11, which is similar to the literature [84]. The GaN epilayer was subsequently grown on sapphire substrates by metal organic chemical vapor deposition (MOCVD) [85]. In Figure 11a, the contact metal was deposited on GaN epilayer.…”
Section: Fabrication Steps Of Vertical Gan Sbdsmentioning
confidence: 93%